Underrepresentation of atopic dermatitis publications in pediatric journals: a bibliometric analysis (Dermatology Reports, 2024)
Extensive research has been published on atopic dermatitis (AD), a prevalent skin condition among pediatricians. To assess the pediatric representation in the most cited literature on AD, using bibliometric analysis. Web of Science citation indexing database was used to identify publications with “atopic” and “dermatitis” or “eczema” in their title. Results were ranked by their Annual citation (AC) and refined to the top 100 most cited articles in the non-refined pediatric category and the top five journals in the categories of general medicine, dermatology, and pediatrics, by impact factor. 28,360 publications were retrieved. The metrics were significantly higher in dermatology, compared to pediatric and general categories [(RTC=0.899, p